2012
DOI: 10.1038/emboj.2012.227
|View full text |Cite
|
Sign up to set email alerts
|

A novel molecular mechanism involved in multiple myeloma development revealed by targeting MafB to haematopoietic progenitors

Abstract: Transgenic expression of the MafB oncogene in haematopoietic stem/progenitor cells induces plasma cell neoplasia reminiscent of human multiple myeloma and suggests DNA methylation as cause of malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 66 publications
3
62
0
Order By: Relevance
“…This result is supported by the increased expression of factors such as MafB that are transiently expressed in endocrine progenitors of the embryonic pancreas. MafB is also upregulated in the dedifferentiated beta cells of beta cellspecific Foxo1 KO mice with metabolic stress and Pdx1 KO mice [8,14], and induces genome-wide changes in DNA methylation [39]. Thus, MafB may be responsible for the upregulation of molecules including those beta cell disallowed genes in dedifferentiated beta cells by inducing epigenetic changes, which have been shown to regulate Slc16a1 expression [35,40].…”
Section: Discussionmentioning
confidence: 97%
“…This result is supported by the increased expression of factors such as MafB that are transiently expressed in endocrine progenitors of the embryonic pancreas. MafB is also upregulated in the dedifferentiated beta cells of beta cellspecific Foxo1 KO mice with metabolic stress and Pdx1 KO mice [8,14], and induces genome-wide changes in DNA methylation [39]. Thus, MafB may be responsible for the upregulation of molecules including those beta cell disallowed genes in dedifferentiated beta cells by inducing epigenetic changes, which have been shown to regulate Slc16a1 expression [35,40].…”
Section: Discussionmentioning
confidence: 97%
“…So far, the functions of MafB have been rarely reported and mainly focus on its roles in islet β cells [16][17][18][19], macrophages [10,[20][21][22][23][24] and multiple myeloma [25][26][27][28][29][30][31]. Here we uncovered its new function in dendritic cell maturation.…”
Section: Mafb Regulated the Phenotypic Maturation Of Dcsmentioning
confidence: 91%
“…We also reported that the promoter activity of MafB is increased in b-cells of diabetes model mice such as db/db mice and mice that have received low-dose streptozotocin (Nishimura et al 2015). Because MafB induces genome-wide changes in DNA methylation (Vicente-Dueñas et al 2012), we speculated the MafB may be a key molecule for the upregulation of b-cell disallowed genes in dedifferentiated b-cells. Thus, we investigated the activity and methylation status of the MafB promoter using an in vitro model of compromised b-cells.…”
Section: Introductionmentioning
confidence: 88%